Distribution Scylla spp. in Estuarine of Donan River, Eastern Segara Anakan, Cilacap: Distribusi Scylla spp. di Perairan Estuari Sungai Donan Segara Anakan Bagian Timur, Cilacap - Sulistiono Sulistiono; Nurul Musyariafah Yahya; Etty Riani (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2021)
Mangrove forests are ecosystems that make up coastal areas and river estuaries. The examples of mangrove ecosystems found in Indonesia are in Segara Anakan, Central Java. One of the aquatic biota with the economic value found in the mangrove forest ecosystem is the mud crab (Scylla spp.). The purpose of this study was to assess the distribution of mangrove crabs (Scylla spp.) to the presence of mangrove species in the mouth of the Donan River, Segara Anakan. A sampling of crabs and observations of mangrove vegetation were carried out at five stations spread from the river to the sea. The results showed that there were three types of mangrove crabs caught in the vicinity of the study, namely Scylla tranquebarica, S. olivacea, and S. serrata. The types of mangroves found include Rhizophora apiculata, R. mucronata, Avicennia rumphiana, A. alba, A. officinalis, and Nypa. Regression analysis showed that mangrove density correlated with the abundance of Scylla tranquebarica and Scylla olivacea, but contradicts the abundance of Scylla serrate. PCA analysis showed that the Crab species Scylla tranquebarica and Scylla olivacea were associated with mangroves of Avicennia alba, Avicennia rumphiana, and Rhizophora apiculata. Meanwhile, Scylla serrata crabs are associated with Avicennia officinalis.